2007
DOI: 10.1016/j.virol.2007.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of equine coronavirus

Abstract: The complete genome sequence of the first equine coronavirus (ECoV) isolate, NC99 strain was accomplished by directly sequencing 11 overlapping fragments which were RT-PCR amplified from viral RNA. The ECoV genome is 30,992 nucleotides in length, excluding the polyA tail. Analysis of the sequence identified 11 open reading frames which encode two replicase polyproteins, five structural proteins (hemagglutinin esterase, spike, envelope, membrane, and nucleocapsid) and four accessory proteins (NS2, p4.7, p12.7, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 87 publications
0
82
1
2
Order By: Relevance
“…Coronavirus-like particles have been identified in the feces of diarrheic foals and horses (Bass and Sharpee, 1975;Durham et al, 1979;Huang et al, 1983;Mair et al, 1990); however, isolation and characterization of these agents were not reported until an ECoV (NC99 strain) was isolated from the feces of a diarrheic foal in North Carolina (Guy et al, 2000). Its complete genomic sequence and phylogenetic studies suggest that ECoV NC99 belongs to the cluster of Betacoronavirus-1 (formerly group 2a coronavirus) and is the most closely related to BCoV, HCoV-OC43, and PHEV (Zhang et al, 2007). However, little is still known about ECoV, especially with regard to the genetic diversity of field strains and their clinical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronavirus-like particles have been identified in the feces of diarrheic foals and horses (Bass and Sharpee, 1975;Durham et al, 1979;Huang et al, 1983;Mair et al, 1990); however, isolation and characterization of these agents were not reported until an ECoV (NC99 strain) was isolated from the feces of a diarrheic foal in North Carolina (Guy et al, 2000). Its complete genomic sequence and phylogenetic studies suggest that ECoV NC99 belongs to the cluster of Betacoronavirus-1 (formerly group 2a coronavirus) and is the most closely related to BCoV, HCoV-OC43, and PHEV (Zhang et al, 2007). However, little is still known about ECoV, especially with regard to the genetic diversity of field strains and their clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…A coronavirus antigen detected by antigen-capture enzyme-linked immunosorbent assay and immunohistochemistry in the feces and intestine of a foal suffering from neonatal enterocolitis have also been reported (Davis et al, 2000); however, isolation and characterization of the causative agent was not successfully performed. An ECoV was isolated from the feces of a diarrheic foal in 1999 (ECoV-NC99) in North Carolina, USA (Guy et al, 2000); its complete genomic sequence is composed of 11 open reading frames (ORFs) encoding two replicase polyproteins, five structural proteins (hemagglutinin esterase [HE], spike [S], envelope [E], membrane [M], and nucleocapsid [N]), and four accessory proteins (ns2, p4.7, p12.7, and I) (Zhang et al, 2007). Antigenic and genomic characterization studies revealed that this virus is a new member of species Betacoronavirus-1.…”
Section: Introductionmentioning
confidence: 99%
“…Equine coronavirus (ECoV) was first identified in the feces of a diarrheic foal. When the amino acid and genome sequences of ECoV were compared with those of other avian and mammalian coronaviruses, ECoV was found to be relatively similar to group II coronaviruses such as murine hepatitis virus (MHV) and human coronavirus (HCoV) OC43 and particularly to bovine coronaviruses (BCoVs) (Guy et al, 2000;Zhang et al, 2007). Although there have been reports on suspected cases of spontaneous ECoV infection showing severe diarrhea, investigations on the pathogenicity of ECoV infection have not been conducted until now.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these genomes were sequenced using the RNA extracted directly from the clinical specimens, such as nasopharyngeal aspirate or stool, as the template, while the viruses themselves were still non-cultivable [2,3,6,[11][12][13][14][15]. This provided more accurate analysis of the in situ viral genomes avoiding mutational bias during in vitro viral replication.…”
mentioning
confidence: 99%